Coenzyme Q10 attenuates platelet integrin αIIbβ3 signaling and platelet hyper-reactivity in ApoE-deficient mice. Issue 1 (22nd November 2019) - Ya, Fuli; Xu, Xiaohong Ruby; Tian, Zezhong; Gallant, Reid C.; Song, Fenglin; Shi, Yilin; Wu, Yinfan; Wan, Jianbo; Zhao, Yimin; Adili, Reheman; Ling, Wenhua; Ni, Heyu; et al.
Abstract : CoQ10 supplementation in ApoE −/− mice attenuates high-fat diet-induced platelet hyper-reactivity via down-regulating platelet αIIbβ3 signaling, and thus protecting against atherothrombosis. Abstract : Coenzyme Q10 (CoQ10) exists in a wide variety of foods and has promising cardiovascular benefits. However, its effects on platelets and integrin αIIbβ3 signaling during atherosclerosis have not been previously explored. Here, apolipoprotein E-deficient (ApoE −/− ) mice were fed a standard diet, high-fat diet (HFD) or CoQ10-supplemented HFD for 12 weeks. We found that CoQ10 supplementation in ApoE −/− mice significantly alleviated formation of HFD-induced atherosclerotic lesions, and attenuated platelet hyper-aggregation and granule secretion, including CD62P, CD63 and CD40 ligand (CD40L) expression and platelet factor-4, β-thromboglobulin and activation normal T cell expressed and secreted (CCL5) release. CoQ10 supplementation decreased soluble fibrinogen and JON/A binding to αIIbβ3 on activated platelets, indicating that αIIbβ3-mediated inside-out signaling was attenuated. Additionally, CoQ10 down-regulated platelet αIIbβ3 outside-in signaling including decreasing phosphorylation of the β3 intracellular tail, cellular and sarcoma tyrosine-protein kinase (c-Src), and myosin light chain (MLC), and consistently attenuating platelet spreading and clot retraction. Importantly, platelet–monocyte aggregation that was primarily mediated by αIIbβ3 and can be blocked using an αIIbβ3-specific antagonist tirofiban was also markedly diminished by CoQ10. Thus, CoQ10 supplementation attenuates platelet hyper-reactivity via down-regulating both αIIbβ3 inside-out and outside-in signaling, which may play important preventive roles in atherothrombosis.